2005
DOI: 10.1111/j.1600-0838.2005.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity resistance and cardiovascular training improve physical capacity in cancer patients undergoing chemotherapy

Abstract: The purpose of the study was to examine the effects of a supervised high- and low-intensity structured training program in cancer patients concurrently undergoing chemotherapy. Seventy patients, in different stages of the disease and with different diagnoses (48 females, 22 males), between 18 and 65 years of age (mean age 42.8) participated in a 9-h weekly training program over 6 weeks. The intervention involved physical exercise, relaxation, massage, and body-awareness training. Physical capacity (one-repetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 43 publications
1
32
1
5
Order By: Relevance
“…In addition, exercise can inhibit catabolic mediators such as cortisol, improving body constitution (Baar and Esser 1999), and to reduce tumor growth promoting improvement of patient state (Westerlind et al 2003;Bacurau et al 2007). It has been reported that 6 weeks of high-intensity power exercise and aerobic training increased body weight and aerobic Wtness in cancer patients undergoing chemotherapy, attenuating some symptoms of cachexia syndrome (Quist et al 2006). In our study, anaerobic training partially prevented the development of cancer cachexia in Walker 256 tumor-bearing rats by reducing tumor growth, lactate and triacylglycerol concentration, body weight loss, PIF expression, and was able to maintain liver glycogen content.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, exercise can inhibit catabolic mediators such as cortisol, improving body constitution (Baar and Esser 1999), and to reduce tumor growth promoting improvement of patient state (Westerlind et al 2003;Bacurau et al 2007). It has been reported that 6 weeks of high-intensity power exercise and aerobic training increased body weight and aerobic Wtness in cancer patients undergoing chemotherapy, attenuating some symptoms of cachexia syndrome (Quist et al 2006). In our study, anaerobic training partially prevented the development of cancer cachexia in Walker 256 tumor-bearing rats by reducing tumor growth, lactate and triacylglycerol concentration, body weight loss, PIF expression, and was able to maintain liver glycogen content.…”
Section: Discussionmentioning
confidence: 67%
“…In one study, muscular strength increased by approximately 41% in patients who participated in a 6-week resistance training program (Quist et al, 2006). Likewise, a 12-month exercise program resulted in increases in upper body muscular strength and lower body endurance in breast cancer survivors (Wiggins & Simonavice, 2008).…”
Section: Muscular Strength and Endurancementioning
confidence: 99%
“…[56][57][58] in aerobic fitness for 79 patients undergoing chemotherapy. 6 More importantly, subjects participating in the nine hours per week training program that lasted 6 weeks also showed an average increase in muscular strength of 41%. Wiggins and Simonavice found upper body muscular strength and lower body endurance increases in 6 breast cancer survivors from baseline to 12 months in a structured exercise program.…”
Section: Physical Functioning/qol Researchmentioning
confidence: 99%
“…4 In addition, research over the last few years has clearly shown cardiorespiratory benefits (increases in aerobic capacity), increases in quality of life (QOL), and increases in physical functioning for cancer survivors who engage in exercise programs. [5][6][7] Furthermore, a 2004 report on diet and nutrition indicated that obesity and/or a sedentary lifestyle (both modifiable through diet and exercise) increases the risk for developing several types of cancer such as breast, colon, kidney, and endometrial cancer. 4 Thus, evidence continues to accumulate through research studies and reviews indicating a link between a physically active healthy lifestyle and improvements in mental and physical QOL in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%